DESORPSI ION LOGAM BESI (Fe) DAN TEMBAGA (Cu) DARI ADSORBEN BIJI PEPAYA DENGAN LARUTAN PENDESORPSI ASAM DAN BASA - Anita Karunia Zustriani (Integrated Lab Journal, 2019)
Research on heavy metals (iron and copper) ions uptake in wastewater using papaya seed powder and the desorption process has been conducted. The purpose of this study was to provide solutions on handling and processing of heavy metal waste in the laboratory. The adsorption and desorption method is used for this purpose. Desorption process using acid and base desorption agents/solutions. The results show that acid solution gives the better outcame in metal ions desorption from the surface of adsorbent. Acid solution used is hydrochloric acid (HCl), the optimum concentration is 0,15 M. In acidic solution (HCl 0,15 M), the percent desorption of iron (Fe) metal ion was 53,66% and the percent desorption of copper (Cu) metal ion was 91,56%.